PENGARUH QUENCHING DAN MEDIA PENDINGIN TERHADAP SIFAT FISIS DAN MEKANIS BAJA PADUAN FE97,99MN1,60C0,41 - Budi Arto; Kimar Turnip (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
The mechanical properties of Fe97,91Mn1,60C0,41 steel alloy have improved, especially hardness after been subjected to various quenching media. Samples were heated at austenite temperature 800oC and 2 hours holding time, then quenched in water, oil, and salt water. The microstructures obtained were used to explain the results using optical microscope. Crystal structure and hardness were studied using X-Ray Diffractometer and Brinell Hardness Test. The hardness values of the quenched samples were 375 HB in salt water media, 257 HB in water media, and 231 HB in oil media. Crystal transformation from FCC -austenit to BCT α-martensit were observed in optical microscope and 2 peak values of XRD test result.